2021
DOI: 10.1017/ice.2021.111
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical outcomes associated with blood culture contamination

Abstract: Objective: To determine patient-specific risk factors and clinical outcomes associated with contaminated blood cultures. Design: A single-center, retrospective case-control risk factor and clinical outcome analysis performed on inpatients with blood cultures collected in the emergency department, 2014–2018. Patients with contaminated blood cultures (cases) were compared to patients with negative blood cultures (controls). Setting: A 509-bed tertiary-care university hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 21 publications
1
25
2
Order By: Relevance
“…Possible factors behind this increase include: the oversight of basic infection control practices by reallocated staff with limited or no experience in intensive care; an inadequate diligence with aseptic techniques due to ICU overcrowding; the urgency of blood sampling among critically ill patients; the implementation of ad hoc standardized protocols that envision the sampling of otherwise unneeded blood cultures; and the inexperience in wearing personal protective equipment (PPE). Contamination of blood cultures has been associated with increased antibiotic exposure, prolonged venous access, additional consultations, laboratory and diagnostic requests, prolonged hospitalizations, costs and intra-hospital mortality [ 17 , 18 ]. The increased rates of contaminated blood cultures suggest, therefore, that the challenges encountered when dealing with ICU patients during the pandemic indeed negatively affected the management of critically ill patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible factors behind this increase include: the oversight of basic infection control practices by reallocated staff with limited or no experience in intensive care; an inadequate diligence with aseptic techniques due to ICU overcrowding; the urgency of blood sampling among critically ill patients; the implementation of ad hoc standardized protocols that envision the sampling of otherwise unneeded blood cultures; and the inexperience in wearing personal protective equipment (PPE). Contamination of blood cultures has been associated with increased antibiotic exposure, prolonged venous access, additional consultations, laboratory and diagnostic requests, prolonged hospitalizations, costs and intra-hospital mortality [ 17 , 18 ]. The increased rates of contaminated blood cultures suggest, therefore, that the challenges encountered when dealing with ICU patients during the pandemic indeed negatively affected the management of critically ill patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequent decrease in false-positive blood cultures may lead to lower resource use, shorter hospital stays, more appropriate use of antibiotics, and perhaps even lower in-hospital mortality. 9 , 12 , 13 , 14 Choosing which threshold probability for a positive culture is acceptable as a cut-off for doing or withholding a blood culture in practice depends on the physicians’ preferences and concerns about the patient. The decision curve analysis showed that our model could provide net benefits across an extensive range of cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The percentage of true-positive blood cultures, disregarding contamination, ranges from 1.4% to 12.2% in ED populations worldwide. 4 , 5 , 6 , 7 , 8 , 9 , 10 Due to these low yields, blood culture outcomes affect treatment decisions in only 0.18–2.8% of patients presenting to the ED with suspected infection. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely diagnosis of LOS and starting antibiotic therapy lower the mortality of LOS [5]. However, the current gold standard for diagnosing LOS is based on the results of blood culture analysis which takes more than 24 hours to obtain the results [6]. Therefore, in clinical practice, the antibiotic therapy starts at the moment of blood culture ordering (often denoted as a Cultures, Resuscitation, and Antibiotics Started Here (CRASH) moment), based on the clinical signs of infection, even though these clinical signs may be nonspecific and inconspicuous [2].…”
Section: Introductionmentioning
confidence: 99%